2008
DOI: 10.1682/jrrd.2007.06.0085
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation modeling of associations among combat exposure, PTSD symptom factors, and Global Assessment of Functioning

Abstract: Abstract-This study used structural equation modeling (SEM) to evaluate the relative strength of associations between combat exposure, four posttraumatic stress disorder (PTSD) symptom factors, and functional impairment as indexed by Global Assessment of Functioning (GAF) scores in a sample of 315 veterans assessed at a Department of Veterans Affairs PTSD clinic. Results showed that the association between combat exposure and GAF scores was fully mediated by PTSD severity. The bestfitting model included dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
30
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 33 publications
8
30
1
2
Order By: Relevance
“…A fairly consistent finding from this research is that although all three symptom clusters tend to predict functioning measures in bivariate analyses, numbing symptoms show the strongest associations with poorer outcome, predicting functioning measures beyond the contribution of reexperiencing and hyperarousal symptoms (Lunney & Schnurr, 2007;Miller, Wolf, Martin, Kaloupek, & Keane, 2008;Riggs, Byrne, Weathers, & Litz, 1998;Ruscio, Weathers, King, & King, 2002;Samper et al, 2004;Schnurr & Lunney, 2008). Despite the value of these findings, all of the studies of veteran samples examining functional impairment and PTSD symptoms have been conducted many years after the trauma.…”
supporting
confidence: 60%
“…A fairly consistent finding from this research is that although all three symptom clusters tend to predict functioning measures in bivariate analyses, numbing symptoms show the strongest associations with poorer outcome, predicting functioning measures beyond the contribution of reexperiencing and hyperarousal symptoms (Lunney & Schnurr, 2007;Miller, Wolf, Martin, Kaloupek, & Keane, 2008;Riggs, Byrne, Weathers, & Litz, 1998;Ruscio, Weathers, King, & King, 2002;Samper et al, 2004;Schnurr & Lunney, 2008). Despite the value of these findings, all of the studies of veteran samples examining functional impairment and PTSD symptoms have been conducted many years after the trauma.…”
supporting
confidence: 60%
“…Thus while re-experiencing symptoms may be critical as indicators of PTSD, they do not appear to play as important a role as the other symptom clusters in the life impact of PTSD. Consistent with prior studies (e.g., Lunney & Schnurr, 2007;Miller et al, 2008), the symptom cluster of numbing / avoidance was significantly associated with higher global severity (month 1) and with less satisfaction with life (month 6), although not uniquely associated with subjective distress. In addition, numbing / avoidance symptoms were uniquely predictive of several indices of interpersonal functioning, including two measures of global social impairment (CAPS item and the LIFE scale), and relationships with friends.…”
Section: Discussionsupporting
confidence: 87%
“…Re-experiencing symptoms, as in previous studies (e.g., Lunney & Schnurr, 2007;Miller et al, 2008), were not uniquely associated with any measures of impairment or distress. Thus while re-experiencing symptoms may be critical as indicators of PTSD, they do not appear to play as important a role as the other symptom clusters in the life impact of PTSD.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…For example, Miller, Wolf, Martin, Kaloupek, and Keane (2008) reported that an increase in combat exposure showed a linear relationship to the severity of PTSD symptoms in their sample of 315 male combat veterans who served predominantly in the Vietnam War. Additionally, Hoge et al (2004) described a linear relationship between the number of firefights in which a soldier had been engaged and the prevalence of PTSD in their sample of OIF/OEF service members.…”
mentioning
confidence: 99%